Cybersecurity Framework for Smart Atmospheric Water Harvesting Systems Powered by Renewable Energy - Radha, P; Kumar, B. Senthil; Padmanabhan, S. (NPRC Journal of Multidisciplinary Research, 2026)
Objective: This paper aims to address the cybersecurity vulnerabilities of smart Atmospheric Water Generators (AWGs) by proposing a secure-by-design architecture that ensures the integrity, availability, and authenticity of sensing, control, and communication processes in renewable-energy-powered water harvesting systems. Methods: The proposed system integrates thermoelectric (Peltier) cooling with multi-stage purification (sediment filtration, activated carbon, UV sterilization) and employs image-processing-based monitoring for real-time condensation analysis, generation rate estimation, and tank-level assessment. A cybersecurity framework is embedded within the IoT–SCADA control stack, incorporating threat modeling, secure communication protocols, device identity and authentication, firmware integrity verification, role-based access control, and anomaly detection based on process and power telemetry. Experimental validation was conducted under varying humidity and temperature conditions, alongside simulated attack scenarios (sensor spoofing, command injection, denial-of-service) to evaluate security resilience. Results: The system demonstrated reliable water production across a range of environmental conditions. Security validation showed enhanced detection and mitigation of common IoT/ICS attack vectors, with improved resilience against data manipulation and control disruptions while maintaining operational performance. Conclusion: The integrated cyber-resilient design supports decentralized, sustainable potable water supply for rural, remote, and disaster-affected regions, offering a robust framework that combines renewable-energy operation with active security monitoring without compromising water production efficiency.